Convalescent plasma therapy as a treatment for COVID-19 - Shankar-Hari, Manu (Henry Stewart Talks, 2020)
What is convalescent plasma therapy, Does this treatment confer long-lasting immunity?, Mechanism of action of therapeutic antibodies, Counterindications with plasma transfusions, The need for lengthy clinical trials, Preliminary assessment of convalescent plasma therapy in a clinical trial, When might this treatment be approved, and how fast can it be delivered?